1983
DOI: 10.1021/ic00168a037
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic circularly polarized luminescence spectra of Eu(.beta.-diketonate)3X2 complexes in nonaqueous solution

Abstract: Unpolarized emission spectra and magnetic field induced circularly polarized emission spectra are reported for EuC13 and for five different tris(|8-diketonate) Eu(III) complexes in methanol and in yV./V-dimethylformamide solutions. Analysis of the EuCl3 spectra suggests the predominance of axially symmetric coordination species with C3v point-group symmetry.Analysis of the tris(/3-diketonate) Eu(III) spectra show the predominance of nonaxially symmetric structures with very strong orthorhombic crystal field co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1984
1984
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…This technique has been used mainly to investigate europium(III) coordination compounds in solution [608][609][610][611][612][613][614]. Table 8 for an example [81]).…”
Section: Magnetic Circular Dichroism (Mcd)mentioning
confidence: 99%
“…This technique has been used mainly to investigate europium(III) coordination compounds in solution [608][609][610][611][612][613][614]. Table 8 for an example [81]).…”
Section: Magnetic Circular Dichroism (Mcd)mentioning
confidence: 99%
“…As discussed above, the 5 D 0 -7 F 2 transition is a forced electric dipole transition and according to the ligand dipole polarization model, its intensity is proportional to the square of the ligand dipolar polarizability. 26 The comparison of the ratio R, i.e., I( 5 D 0 -7 F 2 )/I( 5 D 0 -7 F 1 ), which has been employed in great detail in many publications with misleading conclusions, is considered under three regimes.…”
Section: Postscriptmentioning
confidence: 99%
“…The absence of splitting of the 5 D 0 → 7 F 0 transition indicated that only one monomeric species exist in solution. Later on Richardson and coworkers (Foster et al, 1983) extended these studies to the complexes [Eu(hfac) 3 ], [Eu(tfac) 3 ], [Eu(bpp) 3 ], [Eu(ftac) 3 ] and [Eu(ftac) 3 (phen)]. MCPL spectra were measured in DMF and in methanol.…”
Section: Photoluminescencementioning
confidence: 99%